Trends and cyclical variation in the incidence of childhood type 1 diabetes in 26 European centres in the 25 year period 1989–2013: a multicentre prospective registration study - Patterson, Christopher C.; Harjutsalo, Valma; Rosenbauer, Joachim; Neu, Andreas; Cinek, Ondrej; Skrivarhaug, Torild; Rami-Merhar, Birgit; Soltesz, Gyula; Svensson, Jannet; Parslow, Roger C.; Castell, Conxa; Schoenle, Eugen J.; et al. (Diabetologia, 2019)
Aims/hypothesis Against a background of a near-universally increasing incidence of childhood type 1 diabetes, recent reports from some countries suggest a slowing in this increase. Occasional reports also describe cyclical variations in incidence, with periodicities of between 4 and 6 years. Methods Age/sex-standardised incidence rates for the 0- to 14-year-old age group are reported for 26 European centres (representing 22 countries) that have registered newly diagnosed individuals in geographically defined regions for up to 25 years during the period 1989–2013. Poisson regression was used to estimate rates of increase and test for cyclical patterns. Joinpoint regression software was used to fit segmented log-linear relationships to incidence trends. Results Significant increases in incidence were noted in all but two small centres, with a maximum rate of increase of 6.6% per annum in a Polish centre. Several centres in high-incidence countries showed reducing rates of increase in more recent years. Despite this, a pooled analysis across all centres revealed a 3.4% (95% CI 2.8%, 3.9%) per annum increase in incidence rate, although there was some suggestion of a reduced rate of increase in the 2004–2008 period. Rates of increase were similar in boys and girls in the 0- to 4-year-old age group (3.7% and 3.7% per annum, respectively) and in the 5- to 9-year-old age group (3.4% and 3.7% per annum, respectively), but were higher in boys than girls in the 10- to 14-year-old age group (3.3% and 2.6% per annum, respectively). Significant 4 year periodicity was detected in four centres, with three centres showing that the most recent peak in fitted rates occurred in 2012. Conclusions/interpretation Despite reductions in the rate of increase in some high-risk countries, the pooled estimate across centres continues to show a 3.4% increase per annum in incidence rate, suggesting a doubling in incidence rate within approximately 20 years in Europe. Although four centres showed support for a cyclical pattern of incidence with a 4 year periodicity, no plausible explanation for this can be given.